An Empirical Study on the Identification of Salesforce Engagement Drivers: A Study of Selected Retail Outlets in Visakhapatnam - Devi Prasad Kotni, V. V.; Karumuri, Venkateswarlu (Prabandhan: Indian Journal of Management, 2015)
Salesforce are the people who are highly responsible for the inflow of revenues in any organization, and the retail sector is not an exception. The study of salesforce engagement in retail outlets would enable the retailers to understand how they can attain better business performance and customer satisfaction. If the needs of the salesforce are properly addressed by the retail managers, the customers' needs in the retail outlets will be addressed properly by the salesforce. Salesforce engagement is one of the practices to address the needs of the employees in a proper manner. But the million dollar question is : How to engage the sales employees ? This study addresses the area of engaging the salesforce in their job of retailing and also attempts to find out the most significant engagement drivers that need to be concentrated upon by the retailers . Sixteen drivers of salesforce engagement were identified, and out of the said drivers, Autonomy-at-Work was identified as the highest ranked driver of salesforce engagement in the retail sector.